STRATEGI PENINGKATAN DAYA TARIK DI DESTINASI TANJUNG BIAS DESA SENTELUK KECAMATAN BATU LAYAR KABUPATEN LOMBOK BARAT - salsabila, elvira hilwa; Astuti, Puja; Ashari, Widya Karisma; Ouktafia, Famira; Wahyudi, Diki; Jailani, Muhammad Aprian; Zitri, Ilham (Magister Administrasi Publik FISIP Universitas Mulawarman, 2023)
Tanjung Bias Beach is one of the beaches in Kenteluk Village, Kec. Batu Layar, West Lombok Regency, the existence of Tanjung Bias Beach has had a big influence on the economy around the Tanjung Bias Beach tourism object. During the Covid-19 Pandemic, tourist visits and local community income decreased drastically. Seeing the development of tourism, there is a need for a good strategy to develop potential energy. tourist attractions on Tanjung Bias Beach. This research uses a qualitative descriptive method, namely describing and analyzing phenomena, events, social conditions, attitudes, perceptions or thoughts of a person individually or in groups and using SWOT analysis, because this research is directed at solving various problems such as opportunities, strengths, weaknesses and threats that exist at the Tanjung Bias Beach tourist attraction. SWOT analysis is the systematic identification of factors for developing strategies. The SWOT analysis compares the external factors Opportunities (opportunities) and Threats (threats) with internal strength factors (strengths) and weaknesses (weaknesses). The Village Government together with the BUMDes Management in Senteluk Village, Batu Layar District, West Lombok Regency are reorganizing and looking for a solution. So that the tourism sector at Tanjung Bias Beach continues to run and develop as it should, one of the ways is by promoting on social media. Media is one of the information links between the government and the community, including information regarding various developments in the tourism sector. Promotional activities by introducing various tourism potentials to introduce tourism products and their uniqueness to tourists and providing understanding and education for local communities and through potential events to introduce Tanjung Bias Beach. Based on the results of interviews, internal factors consist of strengths and weaknesses. These strengths are beautiful natural panoramas, horse attractions, close to the city center and have adequate security, have culinary delights. Weaknesses are parking fees and fraud, road conditions are not good, it is not yet a major tourist destination and not many people know about access and external factors consist of opportunities and threats. These opportunities are creative industries from the community and the existence of various culinary businesses. Meanwhile, the threat is competition between tourist attractions.